CT Urology에서 가돌리늄 조영제 제거를 위한 이중에너지 CT의 Virtual Non-Contrast 기술의 평가 - 조원우(Won-Woo Cho), 송현석(Hyeon-Seok Song), 심지나(Ji-Na Shim), 김령희(Ryung-Hee Kim), 안치복(Chi-Bok An), 김세영(Sei-Young Kim) (대한CT영상기술학회지, 2024)
MRI 조영검사를 시행한 환자의 비뇨기계에 잔존한 가돌리늄 조영제는 CT 영상에서 높은 HU로 나타나 CT Urology를 시행하는데 제한을 주고 있다. 본 연구는 이러한 문제를 해결하기 위해 이중에너지 CT(Dual-Energy Computed Tomography; DECT)의 가상 비 조영상(Virtual Non Contrast; VNC) 기술에 주목하여 다양한 이중에너지에서 VNC를 실제 CT Urology에 적용할 수 있는지 평가하였다. MRI 조영검사를 시행하고 CT Chest 비 조영검사를 시행한 환자의 신장 측 요관에 잔존한 가돌리늄 조영제의 HU값을 측정하였다. 그 결과를 바탕으로 가돌리늄 조영제 혼합물 Max, Mean, Min Mixture를 만들어 생리식염수와 함께 팬텀에 삽입하여 에너지별로 스캔하였다. 또한, Iodine Mixture와 요로결석의 HU를 표현한 Virtual Stone을 제작하여 평가하였다. 그 결과, 70 kV와 sn150 kV를 사용한 DECT의 VNC에서 가돌리늄 조영제 혼합물의 대조도가 현저하게 감소하였으며, Min Mixture는 Normal Saline과 HU와 CNR 모두 거의 유사한 형태로 나타났으며, 요오드 조영제와 가상 요로결석과의 구별도 가능했다. 따라서 MRI 조영검사 1시간 30분의 대기시간을 가지고 CT Urology를 시행할 경우, DECT의 VNC를 활용하여 효과적인 가돌리늄 조영제를 제거한 영상을 획득할 수 있음을 확인했다. Residual gadolinium contrast agents in the urinary tract following MRI contrast-enhanced examinations often presents as elevated Hounsfield Unit (HU) values on CT scans, impeding the efficacy of CT urology procedures. This study aims to explore the feasibility of addressing this challenge through the application of the Dual-Energy Computed Tomography (DECT) Virtual Non-Contrast (VNC) technique across various energy levels. HU values of residual gadolinium contrast agent in the renal pelvis and ureter were measured in patients who underwent MRI contrast-enhanced examinations followed by non-contrast CT chest examinations. Subsequently, gadolinium contrast agent mixtures, such as Max, Mean, and Min Mixtures, were created and scanned together with normal saline using DECT at various energy levels. Additionally, an iodine mixture and a virtual stone representing urolithiasis were fabricated and evaluated. The results demonstrated a significant reduction in contrast enhancement of gadolinium contrast agent with DECT VNC at 70 kV and Sn150 kV. The Min Mixture closely resembled normal saline in both HU and Contrast-to-Noise Ratio (CNR), facilitating the differentiation between iodine contrast agent and virtual urolithiasis. Therefore, utilizing DECT VNC after a 1-hour and 30-minute interval following MRI contrast-enhanced examinations effectively eliminates gadolinium contrast agents, improving the efficacy of CT Urology imaging procedures. KCI Citation Count: 0